Comparison of lipidomic profiling and spatial distribution in brain of a genetic mouse model of Alzheimer's disease using DESI Imaging Mass Spectrometry: regional lipid dyshomeostasis in AD. (20th December 2022) - Lazarian, Artur; Costa, Ana Paula; Fowler, Brandon; Zandkarimi, Fereshteh; McIntire, Laura Beth
Abstract: Background: Alzheimer's disease (AD) is one of the biggest health challenges worldwide. It is culpable for millions of deaths annually, the annual associated costs reach many billions, and these trends are expected to increase dramatically over the next decades. Yet, the underlying cause of AD is not yet understood and therefore no effective treatment is available to date. Lipidomic data from autopsy brain, human plasma and animal models highlight severe lipid dyshomeostasis in AD. Specifically, previous studies have shown that the loss of polyunsaturated fatty acids among multiple phospholipid classes is common in AD affected human brain and mouse models. Thus, the disruption of lipid metabolism and the homeostasis are thought to play a crucial role in the development of AD pathology. It is likely then, that specific pathways in lipid metabolism underlie AD disease mechanisms leading to clinical impairment. Therefore, in order to understand the full etiology and progression of disease, it is critical to identify specific and regionally dysregulated lipid species in both healthy and AD affected brain tissues. Method: In order to interrogate differences in the lipid species between brains from WT and a genetic mouse model of AD across aging, DESI Imaging Mass Spectrometry (IMS) was used to detect regional composition of brain tissue with the Synapt G2‐Si (Waters). We have successfully developed a workflow for quantitative and qualitative lipidomics profiling for mouse brains by using 10µm coronal‐cut brain slices at 60µm resolution. Result: In this study, we compared the brains of WT and AD mice of different ages, namely 8, 12 and 22 years old. By applying DESI IMS, we have shown regional dysregulation of specific lipid species in different brain areas including specific early changes in the hypothalamus region of the mouse brain. Conclusion: We have shown that certain ions, such as m/z 327.233 which corresponds with the polyunsaturated fatty acid DHA, is highly abundant in the putative hypothalamus region of AD mouse brains of various ages compared to that of the wild type. This suggests early and persistent dysregulation of polyunsaturated lipid content associated with genetic drivers of AD in a mouse model.